2011
DOI: 10.1155/2011/542487
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors Influencing Foraging Activity in the Social WaspPolybia paulista(Hymenoptera: Vespidae: Epiponini)

Abstract: Foraging behavior in social wasps is important in the development of the colony and reflects an important ecological interaction between the colony and the environment. Although the social traits of the colony play a role in the foraging activities, the conditions that establish the space and time limits are mainly physical. Here, we evaluate colonies of Polybia paulista throughout one year in order to verify the foraging activities and the items collected, as well as the importance of temperature, relative hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 19 publications
1
14
0
2
Order By: Relevance
“…; Jandt et al. ; Canevazzi & Noll ). Our experimental trials took place over a period of 30 d. During this time, there were fluctuations in temperature, and indeed, temperature was a strong predictor of departure rates during the unmanipulated baseline periods.…”
Section: Discussionmentioning
confidence: 99%
“…; Jandt et al. ; Canevazzi & Noll ). Our experimental trials took place over a period of 30 d. During this time, there were fluctuations in temperature, and indeed, temperature was a strong predictor of departure rates during the unmanipulated baseline periods.…”
Section: Discussionmentioning
confidence: 99%
“…V. crabro is also active with low light intensity but in a higher propensity (Kelber et al, 2011). Second, the worker activity is driven by weather conditions that is quite classical in Vespidae (Canevazzi & Noll, 2011;de Castro, Guimaraes, & Prezoto, 2011;Cruz, Giannotti, Santos, Bichara Filho, & Resende, 2006;Kasper, Reeson, Mackay, & Austin, 2008;da Rocha & Giannotti, 2007). The observed enhancement of the hornet activity during the day with a maximum around noon, already observed by video analysis , can be either attributed to an increase in temperature or in UVB solar irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with Epiponini colonies have shown that seasonal differences in foraging rates are associated with the stage of colony development (Gobbi & Machado, 1985, 1986Paula et al, 2003). A major factor that has not been evaluated in this study is the number of immature of each nest collected, since prey provide protein for the development of the offspring, so the amount of prey captured by foragers is an indirect measure of the number of immature and, consequently, the colony's demand for protein (Canevazzi & Noll, 2011). However, we believe that since this material can be stored in the colony to meet future demand, maybe the number of preys stockpiled does not represent a relation with the number of immature present in the nest at that moment.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table 1, colonies of wasps with stocked material were collected in warmer and humid times of the year, which is an ideal condition for termite colonies to release winged (Mill, 1983;Medeiros et al, 1999;Costa-Leonardo, 2002). Indeed, studies with colonies of P. paulista show that their foraging activity is mainly influenced by variation of temperature and relative humidity (Canevazzi & Noll, 2011). Similarly, in termites, the triggers for the release of winged on reproductive flights include, temperature, humidity, soil moisture and atmospheric pressure (Costa- Lima, 1938), as well as seasonality, meteorological and social changes, colony size, and physiological factors (Costa-Leonardo, 2002).…”
Section: Resultsmentioning
confidence: 99%